A Comparative Study of the Sino-African Civil Wars and its Peaceful Settlements: A case study of the Central African Republic - Nzabana, Vincent; Zhi, Huang feng (Technium Social Sciences Journal, 2021)
Civil war is armed violence perpetrated by civilians. Its objective is the exercise or seizure of power. It takes place within a national territory, involving the participation of the population. It is carried out by means of arms either between armed groups or between different communities. The civil wars of China and Africa are quite unique insofar as the People's Republic of China and Africa were not only colonized but also experienced civil wars in their respective territories and the CAR is nonetheless exempt from this situation. This study tries to understand the difficulties of constructing the nation-state, violating recurrent post-conflict political instability on the one hand, and on the other hand, it helps to determine the problems of building a partnership relationship. The first part highlights the environmental and character aspects of civil wars by taking seriously the difficulties encountered in the construction of the nation state. The second part deals with the peaceful settlement of civil wars in China as well as in Africa with the mechanisms implemented in general and in CAR in particular.